Peran Badan Pemulihan Aset di Kejaksaan Negeri Donggala - Andika Maulana Syah Putra; Ronny Max Hendra; Rato, Dominikus; Ohoiwutun, Y.A. Triana (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research explains the role of the Asset Recovery Agency (formerly known as the